ANALISIS MARGIN dan STRATEGI PEMASARAN TOMAT DI PERUSAHAAN PACET SEGAR DESA CIHERANG KECAMATAN PACET KABUPATEN CIANJUR JAWA BARAT - Miftah, Himmatul (Universitas Djuanda, 2011)
The level of competition among suppliers of tomato is very tight. Furthurmore with the flood of imported products. In order to maintain continuity of its business, the company seeks to develop its business strategy. Research in fresh Pacet Company by analyzing internal and external factors known at the position of growth strategies through a strategy of concentration by implementing horizontal integration strategies or stability. This strategy is supported by the analysis of marketing margins in order to strengthen the company's strategy in gaining a profit.